Role of glycated hemoglobin in microvascular complications in type 2 diabetes mellitus: cross sectional study - Deepika Puri; Jaspreet Kaur; Naveen Gaur; Satyanath Reddy Kodidala (Mìžnarodnij Endokrinologìčnij Žurnal, 2022)
Background. Diabetes mellitus (DM) is a complex disorder which defects mainly vascular complications. Complications increase the morbidity and mortality associated with the disease, reducing life expectancy by 10–15 years. Diabetic neuropathy (DN) is a frequent complication of DM and is defined as the presence of peripheral nerve dysfunction after exclusion of other causes. Poor glycaemic control and chronic hyperglycaemia are the major risk factors for DN. Most important treatment of DN remains good glucose control generally noted as HbA1c ≤ 7.5 %. The purpose of this cross-sectional study is to investigate the role of glycated hemoglobin in microvascular complications in type 2 diabetes mellitus. Materials and methods. This cross-sectional study was carried out in Teerthanker Mahaveer Medical College and Research Center, Moradabad from Jan 2016 to December 2016 in which 100 type 2 diabetic mellitus (T2DM) patients in the age group of 35–69 years were included. Patients were divided into 2 groups of 50 each. Group 1 constituted of T2DM patients without any microvascular complication and group 2 includes T2DM patients with microvascular complications. Examination of patients included recording of medical history, pulse rate and blood pressure. Neuropathy was assessed by clinical examination based on modified NDS procedure, which included examination of vibration, pin prick sensation, temperature sensation on dorsum of foot and Achilles tendon reflex. Blood samples were collected by venepuncture and accordingly biochemistry analysis was carried out (Fasting Blood Glucose, post prandial blood glucose and HbA1c were recorded). HbA1c estimation was done by using COBAS fully automated analyser. Results. Among recruited patients, Mean fasting, PPBS level, HbA1c among test group was significantly more than control group. In control group significant correlation of HbA1c is found with age, weight and BMI and in test group significant correlation of HbA1c is observed with age and duration of DM. Significant correlation of HbA1c with FBS and PPBS seen in both control group and in test group. Among test group, 19 patients were found to have DN and significant correlation of HbA1c is observed with NDS score. Conclusions. Increased HbA1c is closely associated with DN in T2DM patients and could be considered as a potent indicator for DN in these patients.